ANALISIS KINERJA SUB DIREKTORAT PATEN KEMENTERIAN HUKUM DAN HAK ASASI MANUSIA - Novinda Serikandi; Mawar (stiatabalong.ac.id, 2023)
ABSTRACT This study examines the performance of the Patent Sub-Directorate is related to several problems in the application system that have not been maximized, understanding of the applicant or patent holder regarding the use of the application, lack of human resources and limited capabilities, as well as the lack of adequate facilities and infrastructure, besides that the complicated classification process hinders performance, certificate delivery is still manual and certificate recipient addresses are not properly updated. The aim of the research is to analyze and describe the performance of the Patent Sub-Directorate of the Ministry of Law and Human Rights. In this study using the theory of organizational performance according to Dwiyanto namely Productivity, Service Quality, Responsiveness, Responsibility and Accountability. The method used in this research is descriptive with a qualitative approach. The results of the research show that productivity can complete activities or programs according to predetermined targets. However, there are still constraints in terms of human resources and limited budgets. Quality of service The Sub Directorate of Patents has provided good service with quality human resources, good cooperation with relevant agencies and adequate facilities and infrastructure. Responsiveness in providing fast and responsive service to the applicant's needs. Optimal responsibility can be seen from the supervisory leadership and implementation of activities according to policy Accountability for each program and activity an accountability report is prepared. The reports periodically include monthly reports, quarterly reports, and annual reports.